Concepts and Reports of Gifted Adolescents on Aspects of Sexuality - Reis, Verônica Lima dos [UNESP]; Maia, Ana Claudia Bortolozzi [UNESP]; Capellini, Vera Lucia Messias Fialho [UNESP] (Common Ground Research Networks, 2020)
Sexuality is a complex experience and it includes, among other things, feelings of affection and love, sexual practices, and sexual and reproductive health. Gifted people may present dyssynchronism in the intellectual and affective development process. This study aims to present data regarding access to information on sexuality, as well as the sexual education of these adolescents. The method involved twelve gifted adolescents (six boys and six girls)—participants of Schoolwide Enrichment at UNESP Bauru/ SP/Brazil—who answered a survey. Results show that family and school are the main sources of information about sexuality; concepts and beliefs about sexuality portray scientific knowledge; male participants exhibit beauty stereotypes regarding a body considered beautiful. The results are considered relevant, especially when eleven of the participants without experience of sexual practices present theoretical and scientific knowledge. Formal and emancipatory sex education can contribute to the psychosocial and affective development of gifted adolescents.
Keywords: Gifted Adolescents; Giftedness; Sexual Education; Sexuality